HUBUNGAN TINGKAT PENGETAHUAN IBUTENTANG KONTRASEPSI SUNTIK DENGAN KEPATUHAN JADWAL PENYUNTIKAN ULANG DI BIDAN PRAKTEK MANDIRI MURTINAWITA PEKANBARU TAHUN 2015 - Febrianti Febrianti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Family planning is an attempt to measure the number and spacing of children wanted. Cics are a way to prevent pregnancy through hormonal injections. Failure of the injectable contraceptive methods caused by delays acceptor to perform repeated injections. To prevent pregnancy if it is done in a timely menner injection KB. Mother accuracy in injection KB influenced by the mothers knowledge about KB injection and supported with the memory of a good mother. This study aims to determine the relationship of the level of knowledge about contraceptives injection syringe with a compliance schedule repeated in BPM Murtinawita Pekanbaru 2015. This type of research used is quantitative analytical method and approach cross sectional study. Where the research was condected in BPM Murtinawita Pekanbaru on 20 february 27 april 2015 with a population of 1873 people and sample of 100 respondents. Technique sampling in this study is the use accidental sampling.From the research that has been conducted by injection 100 KB acceptor obtained a large part of high knowledgeable about injectable contraceptives as much as 55% (55 people). And the level of compliance is not obedient in doing the re-injection schedule as many as 57% (57 people). From of the statistical test chi-square test is it was found that there was no Relationship of the Level of Knowledge About Contraceptives Injection Syringe With a Compliance Schedule Repeated in BPM Murtinawita Pekanbaru year 2015. Conclusions from the study that there is no relation between knowledge the higher acceptor adherence to the re- injection schedule.There fore ecpected to acceptor to improve compliance in conducting repeated injections with a mark on the calendar according to the date the injection at home again in order not to forget.